Occurrence of second primary malignancies in patients with neuroendocrine tumors of the digestive tract: A case report - Pirozzi, Angelo (Medicine (Baltimore), 2019)
RATIONALE: There is an association between the presence of neuroendocrine neoplasms and incremented risk to develop second primary malignancies. This risk is estimated to be 17%. The most common secondary neoplasms were found in the Gastrointestinal and Genitourinary tracts. PATIENT CONCERNS: A 74-year-old Caucasian patient with melaena came to our observation in June 2015. The Esophago-gastro-duodenoscopy exam found a polypoid formation in the duodenal bulb. Histopathological examination showed a well-differentiated neuroendocrine neoplasm (G1). DIAGNOSIS: During the follow up for the neuroendocrine neoplasm, a CT scan was performed in August 2016 describing infiltration of the right renal sinus and the third proximal ureter segment with heterogeneous enhancement of vascular structure. An US-guided biopsy was conclusive for a Diffuse Large B Cell Lymphoma. In October 2016, a colonoscopy showed a neoplastic lesion at 20 cm from the anal orifice. The Histology exam was positive for an adenocarcinoma with a desmoplastic stroma infiltration. INTERVENTIONS: In November 2016, the patient underwent a left hemicolectomy: the pathologic staging described a G2 adenocarcinoma pT3N1b. In May 2018, the Octreotide scan was negative. In the same month, the patient started a treatment based on 6 cycles of Rituximab, Oxaliplatin, and Capecitabine due to the persistence of lymphomatous disease and hepatic metastases. In July 2018, other 3 cycles of the same treatment were scheduled. OUTCOMES: In January 2019, due to an increase in liver metastases’ size, it was decided to start a new regimen for the colon cancer with FOLFIRI+Cetuximab. The patient is still in treatment with this regimen in April 2019. LESSONS: The risk of a second primary tumor is increased among patients older than 70. Therefore, it is necessary to follow them using total body CT scan and endoscopic techniques of gastrointestinal and genitourinary tracts, not only for the evaluation of the neuroendocrine tumor but also for the higher risk to develop other neoplastic diseases.